The Urgency of Debtor Protection from Misbruik Van Omstandigheden Carried Out by Creditors in the Implementation of Viat Parate Execution of Mortgage Collateral Objects - Amalia, Ayu Zahrina (TABELLIUS: Journal of Law, 2023)
.